Nilai-Nilai Ilahiah dalam Hukum di Indonesia - Fathul Aminudin Aziz (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2020)
Intellectual honesty represent significant spiritual value that has been reserved by the people in Indonesia. Mean while, there are many religions and some societies exploit the variety of those interpretations.